Optical element and manufacturing method thereof
By using liquid crystal layers with different glass transition points in optical elements, the problem of delay variation on the curvature surface is solved, and the stability of optical performance is improved.
Patent Information
- Application Number
- JP2022541562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-07
- Filing Date
- 2021-08-03
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-08-03
AI Technical Summary
In the prior art, the delay variation problem of optical elements on the curvature surface leads to unstable optical performance.
Optical elements with transparent substrate and liquid crystal layer are used, and the glass transition points of the slow axis and fast axis are set to different temperatures respectively to control the delay characteristics of the liquid crystal layer and reduce the delay variation on the curvature surface.
It effectively reduces the delay variation of optical elements on the curvature surface and improves the stability of optical performance.
Smart Images

Figure 0007666513000009 
Figure 0007666513000010 
Figure 0007666513000011
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an optical element and a method for manufacturing the same. [Background technology]
[0002] The curved polarizing plate described in Patent Document 1 has a polarizer and a protective film laminated on the polarizer. The protective film has a retardation film. The retardation film is a stretched film and contains polycarbonate (PC) resin as a main component. The curved polarizing plate is attached to the curved surface of a lens to obtain a polarized lens. The polarized lens is used, for example, as sunglasses or a camera lens.
[0003] Patent Document 2 describes a lens having a linear polarizer and a retardation plate. The retardation plate is, for example, a quarter-wave plate. The linear polarizer and the quarter-wave plate form a circular polarizer. The retardation plate is made of cycloolefin copolymer (COC) resin or the like. The retardation plate may be made of a liquid crystal polymer instead of a COC resin. The linear polarizer and the retardation plate are bent separately at high temperature and bonded with an adhesive. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2016-200731 [Patent Document 2] Japan Special Publication No. 2013-519108 Summary of the Invention [Problem to be solved by the invention]
[0005] The optical element includes a lens and a retardation plate. The retardation plate includes a transparent substrate and a liquid crystal layer formed on the transparent substrate. Depending on the application of the optical element, it is desirable for the lens to have a curved surface from the viewpoint of performance.
[0006] One aspect of the present disclosure provides a technique for reducing the variation in retardation of a phase difference plate that curves along the curved surface of a lens. [Means for solving the problem]
[0007] An optical element according to an embodiment of the present disclosure includes a lens having a curved surface and a retardation plate curved along the curved surface. The retardation plate includes a transparent substrate and a liquid crystal layer formed on the transparent substrate. The retardation plate has a slow axis and a fast axis. A glass transition point Tgne of the retardation plate in the slow axis direction is greater than a glass transition point Tgno of the retardation plate in the fast axis direction. Effect of the Invention
[0008] According to one aspect of the present disclosure, it is possible to reduce the variation in retardation of a phase difference plate that curves along the curved surface of a lens. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1(A) is a cross-sectional view showing a state before a retardation plate and a lens of the optical element according to the first embodiment are bonded together, FIG. 1(B) is a cross-sectional view of the optical element obtained by bonding the retardation plate and the lens shown in FIG. 1(A), and FIG. 1(C) is a plan view of the optical element shown in FIG. 1(B). [Diagram 2] FIG. 2(A) is a cross-sectional view showing an optical element according to a first modified example of the first embodiment, FIG. 2(B) is a cross-sectional view showing an optical element according to a second modified example of the first embodiment, and FIG. 2(C) is a cross-sectional view showing an optical element according to a third modified example of the first embodiment. [Diagram 3] FIG. 3(A) is a perspective view showing an example of a transparent substrate and an alignment layer, and FIG. 3(B) is a perspective view showing an example of liquid crystal molecules aligned by the alignment layer shown in FIG. 3(A). [Figure 4] FIG. 4(A) is a plan view showing buckling of a retardation plate of an optical element according to a first embodiment, and FIG. 4(B) is a cross-sectional view taken along line BB in FIG. 4(A). [Diagram 5]Figure 5(A) is a cross-sectional view perpendicular to the Y-axis direction of an optical element relating to a second reference embodiment, Figure 5(B) is a cross-sectional view perpendicular to the X-axis direction of the optical element of Figure 5(A), and Figure 5(C) is a plan view of the optical element of Figure 5(A). [Figure 6] 6A is a diagram of the liquid crystal molecule at point P101 in FIG. 5 as viewed from the Y-axis direction, and FIG. 6B is a diagram of the liquid crystal molecule at point P101 in FIG. 5 as viewed from the X-axis direction. [Figure 7] 7A is a diagram of the liquid crystal molecule at point P103 in FIG. 5 as viewed from the Y-axis direction, and FIG. 7B is a diagram of the liquid crystal molecule at point P103 in FIG. 5 as viewed from the X-axis direction. [Figure 8] FIG. 8 is a diagram showing an example of the relationship between the tilt angle of the flat liquid crystal layer and Rd. [Figure 9] FIG. 9 is a plan view of the optical element according to the second embodiment. [Figure 10] FIG. 10A is a cross-sectional view showing an example of dry etching, and FIG. 10B is a cross-sectional view showing another example of dry etching. [Figure 11] FIG. 11(A) is a cross-sectional view showing the state before the retardation plate and lens of the optical element relating to the third reference embodiment are bonded together, FIG. 11(B) is a cross-sectional view showing the optical element formed by bonding the retardation plate and lens shown in FIG. 11(A), and FIG. 11(C) is a plan view showing the Rd distribution of the optical element shown in FIG. 11(B). [Figure 12] FIG. 12(A) is a cross-sectional view showing a state before a retardation plate and a lens of an optical element relating to a modified example of the third reference form are bonded together, FIG. 12(B) is a cross-sectional view showing an optical element obtained by bonding the retardation plate and the lens shown in FIG. 12(A), and FIG. 12(C) is a plan view showing the distribution of Rd of the optical element shown in FIG. 12(B). [Figure 13] Figure 13(A) is a cross-sectional view of an optical element according to the third embodiment, Figure 13(B) is a cross-sectional view showing an enlarged view of region B of Figure 13(A), and Figure 13(C) is a cross-sectional view showing an enlarged view of region C of Figure 13(A). [Figure 14]Figure 14(A) is a cross-sectional view of an optical element related to a modified example of the third embodiment, Figure 14(B) is a cross-sectional view showing an enlarged view of region B of Figure 14(A), and Figure 14(C) is a cross-sectional view showing an enlarged view of region C of Figure 14(A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. In each drawing, the same or corresponding configurations are denoted by the same reference numerals, and descriptions thereof may be omitted. In addition, in the specification, a numerical range indicated by "~" means that the numerical range indicated before and after the range includes the lower and upper limits.
[0011] (First embodiment) An optical element 1 according to a first embodiment will be described with reference to Fig. 1. In terms of performance, it is desirable for the lens 2 of the optical element 1 to have a curved surface 21 depending on the application.
[0012] The optical element 1 includes a lens 2. The lens 2 may be a spherical lens or an aspherical lens. The lens 2 may be any one of a biconcave lens, a plano-concave lens, a concave meniscus lens, a biconvex lens, a plano-convex lens, and a convex meniscus lens.
[0013] The lens 2 has a curved surface 21. The curved surface 21 has a radius of curvature of, for example, 10 mm to 100 mm on the entire surface or a part of the surface. The radius of curvature of the curved surface 21 is preferably 20 mm to 80 mm, and more preferably 50 mm to 70 mm. The curved surface 21 is a concave surface, for example, as shown in Fig. 1(A) and Fig. 1(B). The concave surface is a curved surface whose center of gravity P0 is recessed from the periphery. In both a cross section perpendicular to the X-axis direction and a cross section perpendicular to the Y-axis direction, the center of gravity P0 of the concave surface is recessed from the periphery of the concave surface. The X-axis direction, the Y-axis direction, and the Z-axis direction are mutually perpendicular. The Z-axis direction is the normal direction at the center of gravity P0 of the concave surface. The XY plane is parallel to the tangent plane at the center of gravity P0 of the concave surface.
[0014] In this embodiment, the curved surface 21 is a concave surface, but may be a convex surface as shown in Fig. 2(B) and Fig. 2(C). A convex surface is a surface in which the center of gravity P0 is more convex (protrudes) than the periphery. In both a cross section perpendicular to the X-axis direction and a cross section perpendicular to the Y-axis direction, the center of gravity P0 of the convex surface is more convex than the periphery of the convex surface.
[0015] The outer shape of the lens 2 is not limited to the circular shape shown in FIG. 1C, but may be, for example, an ellipse or a polygon (including a rectangle).
[0016] The lens 2 may be made of resin or glass. The resin of the resin lens is, for example, polycarbonate, polyimide, polyacrylate, or cyclic olefin. The glass of the glass lens is, for example, BK7 or synthetic quartz.
[0017] The optical element 1 includes a retardation plate 3. The retardation plate 3 is curved along the curved surface 21 of the lens 2. The retardation plate 3 includes, for example, a transparent substrate 4, an alignment layer 5 formed on the transparent substrate 4, and a liquid crystal layer 6 formed on the alignment layer 5. However, the alignment layer 5 may be of any configuration and may be omitted.
[0018] The retardation plate 3 has a slow axis and a fast axis. When viewed in the Z-axis direction, the slow axis is in the X-axis direction and the fast axis is in the Y-axis direction. The slow axis is the direction in which the refractive index is greatest, and the fast axis is the direction in which the refractive index is smallest.
[0019] The retardation plate 3 is, for example, a quarter-wave plate. A quarter-wave plate may be used in combination with a linear polarizing plate (not shown). The absorption axis of the linear polarizing plate and the slow axis of the quarter-wave plate are arranged to be shifted by 45°. The linear polarizing plate and the quarter-wave plate constitute a circular polarizing plate.
[0020] The linear polarizer may be disposed on the opposite side of the retardation plate 3 to the lens 2, or may be disposed between the retardation plate 3 and the lens 2, or may be disposed on the opposite side of the retardation plate 3 to the lens 2.
[0021] 1(B), the retardation plate 3 includes a transparent substrate 4, an alignment layer 5, and a liquid crystal layer 6 in this order from the lens 2 side. Alternatively, as shown in FIGS. 2(A) and 2(C), the retardation plate 3 may include a liquid crystal layer 6, an alignment layer 5, and a transparent substrate 4 in this order from the lens 2 side.
[0022] The transparent substrate 4 is composed of, for example, a glass substrate or a resin substrate. The glass substrate or the resin substrate may have a reflecting or absorbing function for one or more of infrared rays, visible light, and ultraviolet rays, and may be configured to transmit light in a specific wavelength band. The transparent substrate 4 may have a single-layer structure of a single substrate, or may have a multi-layer structure in which a film that imparts a reflecting or absorbing function is laminated on a main substrate (glass substrate or resin substrate) to transmit light in a specific wavelength band. In addition, the transparent substrate 4 may be laminated with a film that imparts a function such as antifouling in addition to the reflecting or absorbing function.
[0023] For example, the transparent substrate 4 may further include a resin film or an inorganic film in addition to a glass substrate or a resin substrate. The resin film is a film having a function such as a color correction filter, a base film such as a silane coupling agent, or an antifouling film. The resin film is formed by, for example, screen printing, vapor deposition, spray coating, or spin coating. The inorganic film is, for example, a metal oxide film having a function as an optical interference film (antireflection or wavelength selection filter). The inorganic film is formed by, for example, sputtering, vapor deposition, or CVD.
[0024] From the viewpoint of bending processability, the transparent substrate 4 is preferably a resin substrate. Specific examples of the resin of the resin substrate include polymethylmethacrylate (PMMA), triacetylcellulose (TAC), cycloolefin polymer (COP), cycloolefin copolymer (COC), polyethylene terephthalate (PET), and polycarbonate (PC).
[0025] The phase difference (retardation) of the transparent substrate 4 is, for example, 5 nm or less, and preferably 3 nm or less. From the viewpoint of reducing the variation in color tone, the phase difference of the transparent substrate 4 is preferably smaller, and may be zero. The phase difference of the transparent substrate 4 is measured, for example, by a parallel Nicol rotation method.
[0026] The glass transition temperature Tgf of the transparent substrate 4 is, for example, 80° C. to 200° C., and preferably 90° C. to 160° C. If Tgf is within the above range, bending workability is good. The glass transition temperature of the transparent substrate 4 is measured, for example, by thermomechanical analysis (TMA).
[0027] The thickness T1 of the transparent substrate 4 (see FIG. 3) is, for example, 0.01 mm to 0.3 mm, preferably 0.02 mm to 0.1 mm, and more preferably 0.03 mm to 0.09 mm. When T1 is within the above range, both bending workability and handleability can be achieved. The thickness T1 of the transparent substrate 4 is measured in the normal direction at each point of the curved surface 21 of the lens 2.
[0028] The alignment layer 5 aligns the liquid crystal molecules in the liquid crystal layer 6. The alignment layer 5 is subjected to a process such as rubbing of polyimide, photolysis of a silane coupling agent or polyimide by irradiation with polarized UV light, use of photodimerization or photoisomerization by irradiation with polarized UV light, use of a fine parallel groove structure, flow alignment process by shear force, or alignment process by oblique deposition of an inorganic material. A combination of multiple processes may be used. Among these, from the viewpoints of alignment control force, applicability to curved surfaces, and reduction of foreign matter, use of photodimerization or photoisomerization by irradiation with polarized UV light or use of a fine parallel groove structure is preferred.
[0029] Materials that undergo photodimerization upon exposure to polarized UV include coumarin, diphenylacetylene, and anthracene. Materials that undergo photoisomerization upon exposure to polarized UV include azobenzene, stilbene, α-imino-β ketoester, and spiropyran. Materials that undergo both photodimerization and photoisomerization upon exposure to polarized UV include cinnamate, chalcone, and stilbazole.
[0030] The alignment layer 5 is coated on the transparent substrate 4. The coating method may be, for example, spin coating, bar coating, dip coating, casting, spray coating, bead coating, wire bar coating, blade coating, roller coating, curtain coating, slit die coating, gravure coating, slit reverse coating, microgravure, or comma coating. The resin composition is applied to the curved surface 21 of the lens 2 and dried. The solvent of the resin composition is removed by heating after application. The coating method may be a vapor deposition method that does not use a solvent.
[0031] The thickness T2 of the alignment layer 5 (see FIG. 3) is, for example, 1 nm to 20 μm, preferably 50 nm to 10 μm, and more preferably 100 nm to 5 μm. The thickness T2 of the alignment layer 5 is measured in the normal direction at each point on the surface of the transparent substrate 4 on which the alignment layer 5 is formed. When the alignment layer 5 has a groove 51, in this specification, the thickness T2 of the alignment layer 5 refers to the distance between the bottom of the groove 51 and the surface of the transparent substrate 4.
[0032] The alignment layer 5 may have a plurality of grooves 51 that are parallel to each other as viewed in the Z-axis direction on the surface in contact with the liquid crystal layer 6 (see FIG. 3(A)). The plurality of grooves 51 are formed, for example, by an imprint method after application of the resin composition. The plurality of grooves 51 are formed, for example, in a stripe pattern.
[0033] When viewed in the Z-axis direction, the longitudinal direction of groove 51 is the X-axis direction, and the width direction of groove 51 is the Y-axis direction. When groove 51 is formed by the imprint method, the dimensions and shape of groove 51 can be controlled with higher precision than when groove 51 is formed by the rubbing method, and the inclusion of foreign matter can also be reduced.
[0034] The depth D of the grooves 51 is, for example, 5 nm to 1000 nm, preferably 10 nm to 300 nm, and more preferably 15 nm to 150 nm. The deeper the depth D of the grooves 51, the stronger the alignment control force of the liquid crystal molecules 61 in the liquid crystal layer 6. The depth D of the grooves 51 may be constant, or may vary as described later.
[0035] The opening width W of the groove 51 is, for example, 5 nm to 800 nm, preferably 20 nm to 300 nm, and more preferably 30 nm to 150 nm.
[0036] The pitch p of the grooves 51 is, for example, 10 nm to 1000 nm, preferably 50 nm to 500 nm, and more preferably 80 nm to 300 nm. The smaller the pitch p, the stronger the alignment control force of the liquid crystal molecules 61 in the liquid crystal layer 6, and the less likely diffracted light is generated.
[0037] 3, the cross section of groove 51 perpendicular to the longitudinal direction (X-axis direction) is rectangular, but may be triangular. The shallower the depth of groove 51, the wider the width. In this case, it is easy to peel off the mold used in the imprint method.
[0038] Materials for forming the groove structure include, for example, energy curable resins such as photocurable resins or thermosetting resins. Photocurable resins are particularly preferred because of their excellent processability, heat resistance, and durability. The photocurable resin composition is, for example, a composition containing a monomer, a photopolymerization initiator, a solvent, and additives (for example, a surfactant, a polymerization inhibitor) as required.
[0039] The glass transition temperature Tg_al of the alignment layer 5 is, for example, 40° C. to 200° C., preferably 50° C. to 160° C., and more preferably 70° C. to 150° C. If Tg_al is within the above range, bending processability is good. The glass transition temperature of the alignment layer 5 is measured, for example, by TMA.
[0040] As described above, the alignment layer 5 may be of any configuration and may be omitted. In that case, the transparent substrate 4 may be subjected to a treatment for aligning the liquid crystal molecules of the liquid crystal layer 6. The treatment may be, for example, rubbing of polyimide, photolysis of a silane coupling agent or polyimide by irradiation with polarized UV light, photodimerization or photoisomerization by irradiation with polarized UV light, flow alignment treatment by shear force, or alignment treatment by oblique deposition of an inorganic material.
[0041] The liquid crystal layer 6 has a slow axis and a fast axis. The retardation Rd is the product of the difference Δn (Δn=ne-no) between the refractive index ne of the slow axis and the refractive index no of the fast axis and the dimension d of the liquid crystal layer 6 in the Z-axis direction. In other words, Rd can be calculated by the formula Rd=Δn×d.
[0042] 3(B), the liquid crystal layer 6 includes a plurality of liquid crystal molecules 61 aligned parallel to one another by the alignment layer 5. As viewed in the Z-axis direction, the long axis direction of the liquid crystal molecules 61 is the X-axis direction, and the short axis direction of the liquid crystal molecules 61 is the Y-axis direction. In this embodiment, the liquid crystal molecules 61 are rod-shaped liquid crystals, but may be discotic liquid crystals.
[0043] The liquid crystal composition used may have a positive or negative wavelength dispersion of the Δn value after curing.
[0044] The liquid crystal composition contains, as a polymerizable compound, for example, compounds represented by the following formulas (a-1) to (a-13).
[0045] [ka]
[0046] [ka]
[0047] [ka] In the above formulae (a-5) and (a-8), n is an integer of 2 to 6. In the above formulae (a-6) and (a-7), R is an alkyl group having 3 to 6 carbon atoms. In the above formulae (a-11), (a-12), and (a-13), n means "normal" and indicates linearity.
[0048] The liquid crystal layer 6 is formed by coating and drying a liquid crystal composition. The liquid crystal composition is, for example, a photocurable polymer liquid crystal containing an acrylic group or a methacrylic group. The liquid crystal composition may contain a component that does not show a liquid crystal phase by itself. It is sufficient that a liquid crystal phase is generated by polymerization. As the component that does not show a liquid crystal phase, for example, a monofunctional (meth)acrylate, a bifunctional (meth)acrylate, a trifunctional or higher (meth)acrylate, etc. are used. The polymerizable liquid crystal composition may contain an additive. As the additive, a polymerization initiator, a leveling agent, a chiral agent, a polymerization inhibitor, an ultraviolet absorber, an antioxidant, a light stabilizer, or a dichroic dye, etc. are used. A plurality of types of additives may be used in combination.
[0049] The liquid crystal composition may be applied by a general method, such as spin coating, bar coating, extrusion coating, direct gravure coating, reverse gravure coating, or die coating. The solvent of the liquid crystal composition is removed by heating after application.
[0050] The solvent of the liquid crystal composition is, for example, an organic solvent. The organic solvent is an alcohol (for example, isopropyl alcohol), an amide (for example, N,N-dimethylformamide), a sulfoxide (for example, dimethyl sulfoxide), a hydrocarbon (for example, benzene or hexane), an ester (for example, methyl acetate, ethyl acetate, butyl acetate, or propylene glycol monoethyl ether acetate), a ketone (for example, acetone, cyclohexanone, or methyl ethyl ketone), or an ether (for example, tetrahydrofuran or 1,2-dimethoxyethane). Two or more kinds of organic solvents may be used in combination. The liquid crystal layer 6 may be formed by a vapor deposition method or a vacuum injection method that does not use a solvent.
[0051] The thickness T3 of the liquid crystal layer 6 (see FIG. 3) is determined based on the wavelength of the light, the phase difference, and Δn (Δn=ne-no). For example, when the wavelength of the light is 543 nm and the phase difference is 1 / 4 wavelength, Rd is 136 nm. When Rd is 136 nm and Δn is 0.1, the thickness T3 of the liquid crystal layer 6 is 1360 nm.
[0052] The thickness T3 of the liquid crystal layer 6 is determined based on the wavelength of light, the phase difference, and Δn as described above, and is not particularly limited, but is, for example, 0.1 μm to 20 μm, preferably 0.2 μm to 10 μm, and more preferably 0.5 μm to 5 μm. The liquid crystal layer 6 is not limited to a ¼ wavelength plate, and may be a ½ wavelength plate, etc.
[0053] The thickness T3 of the liquid crystal layer 6 is measured in the normal direction at each point on the surface of the transparent substrate 4 on which the liquid crystal layer 6 is formed. When the alignment layer 5 has a groove 51, in this specification, the thickness T3 of the liquid crystal layer 6 refers to the distance between the bottom of the groove 51 and the surface of the liquid crystal layer 6 on the opposite side to the transparent substrate 4.
[0054] The glass transition temperature Tg_a of the liquid crystal layer 6 is, for example, 50° C. to 200° C., and preferably 80° C. to 180° C. If Tg_a is within the above range, bending processability is good. The glass transition temperature Tg_a of the liquid crystal layer 6 is measured, for example, by TMA.
[0055] The thickness T4 of the retardation plate 3 is not particularly limited, but is, for example, 0.011 mm to 0.301 mm, preferably 0.021 mm to 0.101 mm, and more preferably 0.031 mm to 0.091 mm. The thickness T4 of the retardation plate 3 is measured in the normal direction at each point on the surface of the transparent substrate 4 on which the liquid crystal layer 6 is formed.
[0056] The retarder 3 may be a broadband retarder further including a second liquid crystal layer laminated on the liquid crystal layer 6, although not shown. The number of liquid crystal layers included in the broadband retarder may be two or more, and may be three or more. When viewed in the Z-axis direction, the multiple liquid crystal layers have slow axes in different directions. When the retarder 3 includes multiple liquid crystal layers, it may include multiple alignment layers, or may have repeated pairs of liquid crystal layers and alignment layers. The multiple alignment layers may have the same material or different materials.
[0057] The retardation of the retarder 3 is not particularly limited, but if it is a quarter-wave plate, it is, for example, 100 nm to 180 nm, preferably 110 nm to 170 nm, and more preferably 120 nm to 160 nm. If the retarder 3 is a half-wave plate, it is, for example, 200 nm to 280 nm, preferably 210 nm to 270 nm, and more preferably 220 nm to 260 nm.
[0058] The broadband retardation plate is, for example, formed by alternately laminating alignment layers 5 and liquid crystal layers 6. The alignment layers 5 and the liquid crystal layers 6 are laminated in this order from the lens 2 side. Note that the broadband retardation plate may be formed by bonding a liquid crystal layer formed on a transparent substrate other than the lens 2 to a liquid crystal layer formed on the lens 2.
[0059] The retardation plate 3 is bent and bonded to the lens 2. The bonding layer 7 is, for example, a transparent optical adhesive (OCA), a liquid adhesive (OSA), polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), cycloolefin polymer (COP), or thermoplastic polyurethane (TPU).
[0060] The phase difference (retardation) of the bonding layer 7 is, for example, 5 nm or less, and preferably 3 nm or less. From the viewpoint of reducing the variation in color tone, the phase difference of the bonding layer 7 is preferably as small as possible, and may be zero. The phase difference of the bonding layer 7 is measured, for example, by a parallel Nicol rotation method.
[0061] The glass transition point of the bonding layer 7 is, for example, −60° C. to 100° C., and preferably −40° C. to 50° C. If the glass transition point of the bonding layer 7 is within the above range, both bending workability and shape conformability can be achieved. The glass transition point of the bonding layer 7 is measured, for example, by TMA.
[0062] The thickness of the bonding layer 7 is, for example, 0.001 mm to 0.1 mm, and preferably 0.005 mm to 0.05 mm. If the thickness of the bonding layer 7 is within the above range, both bending workability and shape followability can be achieved. The thickness of the bonding layer 7 is measured in the normal direction at each point on the curved surface 21 of the lens 2.
[0063] The retardation plate 3 and the lens 2 are bonded together while being heated. The heating temperature is set based on the glass transition temperature Tgf of the transparent substrate 4, and is set within a range of, for example, (Tgf-10)°C or more and (Tgf+30)°C or less, and is preferably set within a range of (Tgf-10)°C or more and (Tgf+20)°C or less. Bonding of the retardation plate 3 and the lens 2 may be performed in a vacuum.
[0064] Alternatively, the retardation film 3 may be placed inside a metal mold for injection molding, and the lens 2 may be injection molded after bending the retardation film 3. When the lens 2 and the retardation film 3 are integrated by in-mold molding, the bonding layer 7 is not necessary.
[0065] Next, buckling of the retardation plate of the optical element according to the first reference embodiment will be described with reference to Fig. 4. The optical element 1A according to the first reference embodiment includes a lens 2A and a retardation plate 3A. The retardation plate 3A includes a transparent substrate 4A, an alignment layer 5A, and a liquid crystal layer 6A. The lens 2A and the retardation plate 3A are bonded together via, for example, a bonding layer 7A.
[0066] Conventionally, when bending the retarder 3A, the alignment layer 5A and the liquid crystal layer 6A are harder than the transparent substrate 4A, and the alignment layer 5A and the liquid crystal layer 6A are less stretchable than the transparent substrate 4A, so that the retarder 3A may buckle. As a result, the liquid crystal layer 6A may become locally thick, and the Rd of the retarder 3A may change locally. Therefore, the color tone may change locally.
[0067] Therefore, in the optical element 1 of this embodiment, Ene / Ef is 0.10 or more and 5.00 or less, and Eno / Ef is 0.10 or more and 5.00 or less. Ef is the Young's modulus of the transparent substrate 4, Ene is the Young's modulus of the retardation plate 3 in the slow axis direction, and Eno is the Young's modulus of the retardation plate 3 in the fast axis direction. Ef, Ene, and Eno are Young's modulus when the temperatures of the transparent substrate 4 and the retardation plate 3 are the glass transition point Tgf of the transparent substrate 4. Ef, Ene, and Eno are measured by TMA.
[0068] When bending the retarder 3, the retarder 3 is heated to a temperature of (Tgf-10)°C or more and (Tgf+30)°C or less, as described above. If Ene / Ef and Eno / Ef are 5.00 or less, the alignment layer 5 and the liquid crystal layer 6 are soft when bending the retarder 3, and the stretchability of the alignment layer 5 and the liquid crystal layer 6 is as good as that of the transparent substrate 4. Therefore, buckling of the retarder 3 can be suppressed, local changes in Rd can be suppressed, and local changes in color tone can be suppressed. On the other hand, if Ene / Ef and Eno / Ef are 0.10 or more, the alignment layer 5 and the liquid crystal layer 6 are appropriately hard when bending the retarder 3. Therefore, the flow of the alignment layer 5 and the liquid crystal layer 6 due to gravity and the flow due to air flow during molding can be suppressed. Preferably, Ene / Ef and Eno / Ef are 0.50 or more and 4.00 or less, and more preferably, Ene / Ef and Eno / Ef are 0.70 or more and 3.00 or less.
[0069] Second embodiment Next, the optical element 1 according to the second embodiment will be described. The diagram of the optical element 1 according to this embodiment is the same as the diagram of the optical element 1 according to the first embodiment, so it will be omitted. Below, the differences from the first embodiment will be mainly described. Note that the technology of this embodiment may be combined with the technology of the first embodiment.
[0070] First, an optical element 1B according to a second reference embodiment will be described mainly with reference to Fig. 5. As shown in Fig. 5(A) and Fig. 5(B), the optical element 1B includes a lens 2B and a retardation plate 3B. The retardation plate 3B includes a transparent substrate 4B, an alignment layer 5B, and a liquid crystal layer 6B. The lens 2B and the retardation plate 3B are bonded together via, for example, a bonding layer 7B.
[0071] The liquid crystal layer 6B includes a plurality of liquid crystal molecules 61 (see FIG. 3B) that are parallel to one another. When viewed in the Z-axis direction, the long axis direction of the liquid crystal molecules 61 is the X-axis direction, and the short axis direction of the liquid crystal molecules 61 is the Y-axis direction.
[0072] The present inventors have found through experiments and the like that when a liquid crystal layer 6B of a uniform thickness is formed on the curved surface 21B of the lens 2B, there is a problem in that the retardation Rd of the liquid crystal layer 6B varies greatly.
[0073] The reason why the above problem occurs when the thickness of the liquid crystal layer 6B is uniform will be described. The liquid crystal layer 6B is formed on the curved surface 21B of the lens 2B, as shown in Figures 5(A) and 5(B). As a result, the liquid crystal molecules 61 are tilted with respect to the XY plane at positions away from the center of gravity P100 of the curved surface 21B.
[0074] The tilt of the liquid crystal molecules 61 is different between points P101 and P102 on the first virtual line L101 and points P103 and P104 on the second virtual line L102 shown in Fig. 5(C). When viewed in the Z-axis direction, the first virtual line L101 is a virtual line that passes through the center of gravity P100 and is parallel to the slow axis. Also, when viewed in the Z-axis direction, the second virtual line L102 is a virtual line that passes through the center of gravity P100 and is parallel to the fast axis.
[0075] Fig. 6 shows the tilt of the liquid crystal molecule 61 at point P101 on the first virtual line L101. In Fig. 6, the dashed line shows the liquid crystal molecule 61 at the center of gravity P100, and the solid line shows the liquid crystal molecule 61 at point P101. As is clear from Fig. 6, at point P101, the dimension in the X-axis direction of the liquid crystal molecule 61 is smaller than that at the center of gravity P100, while the dimension in the Y-axis direction of the liquid crystal molecule 61 remains unchanged. The same is true at point P102.
[0076] As a result, at points P101 and P102 on the first virtual line L101, ne becomes smaller compared to the center of gravity P100, and no remains unchanged, so Δn becomes smaller. Also, d becomes larger at points P101 and P102 compared to the center of gravity P100. The decrease in Rd due to the decrease in Δn is greater than the increase in Rd due to the increase in d. As a result, Rd, which is the product of Δn and d, becomes smaller at points P101 and P102 compared to the center of gravity P100.
[0077] Fig. 7 shows the tilt of the liquid crystal molecule 61 at point P103 on the second virtual line L102. In Fig. 7, the dashed line shows the liquid crystal molecule 61 at the center of gravity P100, and the solid line shows the liquid crystal molecule 61 at point P103. As is clear from Fig. 7, at point P103, the dimension of the liquid crystal molecule 61 in the Y axis direction is slightly smaller than that at the center of gravity P100, while the dimension of the liquid crystal molecule 61 in the X axis direction remains unchanged. The same is true at point P104.
[0078] As a result, at points P103 and P104 on the second virtual line L102, no is smaller than at the center of gravity P100, and ne remains unchanged, so Δn is larger. Also, at points P103 and P104, d is larger than at the center of gravity P100. Therefore, Rd is larger at points P103 and P104 than at the center of gravity P100.
[0079] An example of the relationship between the tilt angle of the flat liquid crystal layer and the measured value of Rd is shown in Figure 8. In Figure 8, a tilt angle of 0° means that the flat liquid crystal layer is aligned parallel to the XY plane.
[0080] The black circles in Fig. 8 represent data obtained by rotating and tilting the flat liquid crystal layer clockwise and counterclockwise around the second virtual line L102. A positive tilt angle means that the rotation direction is clockwise. A negative tilt angle means that the rotation direction is counterclockwise.
[0081] 8 corresponds to the distance between the center of gravity P100 and points P101, P102 on the first virtual line L101. The greater the distance between the center of gravity P100 and points P101, P102, the greater the absolute value of the tilt angle of the liquid crystal molecules 61 and the smaller Rd.
[0082] 8 represent data obtained by rotating and tilting the flat liquid crystal layer clockwise and counterclockwise around the first virtual line L101. A positive tilt angle means that the rotation direction is clockwise. A negative tilt angle means that the rotation direction is counterclockwise.
[0083] 8 corresponds to the distance between the center of gravity P100 and points P103, P104 on the second virtual line L102. The greater the distance between the center of gravity P100 and points P103, P104, the greater the absolute value of the tilt angle of the liquid crystal molecules 61 and the greater Rd.
[0084] 8, the tendency of change in Rd is different between the first virtual line L101 and the second virtual line L102. On the first virtual line L101, the greater the distance from the center of gravity P100, the smaller Rd becomes. On the other hand, on the second virtual line L102, the greater the distance from the center of gravity P100, the larger Rd becomes.
[0085] In this embodiment, the curved surface 21B of the lens 2B is a concave surface, but may be a convex surface. The absolute values of the tilt angles of the liquid crystal molecules 61 are approximately the same for the convex surface and the concave surface. Therefore, the distribution of Rd is approximately the same for the convex surface and the concave surface.
[0086] Conventionally, there was a large difference in Rd between points P101 and P102 on the first imaginary line L101 and points P103 and P104 on the second imaginary line L102. This is clear from a comparison of the black circles and white circles in FIG.
[0087] Therefore, in this embodiment, in order to make the white circles in FIG. 8 closer to the black circles, the thickness of the liquid crystal layer 6 at points P103 and P104 on the second virtual line L102 is made thinner than the thickness of the liquid crystal layer 6 at points P101 and P102 on the first virtual line L101.
[0088] The thickness distribution of the liquid crystal layer 6 is controlled by, for example, the anisotropy of the elongation of the retarder 3 during bending. The anisotropy of the elongation of the retarder 3 during bending can be controlled by the difference between Tgne and Tgno. Tgne is the glass transition point of the retarder 3 in the X-axis direction, and Tgno is the glass transition point of the retarder 3 in the fast axis direction.
[0089] In the optical element 1 of this embodiment, Tgne is greater than Tgno. When bending the retardation plate 3, the retardation plate 3 is heated to a temperature of (Tgf-10)°C or more and (Tgf+30)°C or less.
[0090] If Tgne is greater than Tgno, the retarder 3 will stretch more in the Y-axis direction than in the X-axis direction during bending of the retarder 3. As a result, the thickness distribution of the liquid crystal layer 6 is optimized, and the difference in Rd is reduced.
[0091] Tgne is, for example, 90° C. or more and 250° C. or less, preferably 120° C. or more and 180° C. or less, and more preferably 130° C. or more and 160° C. or less. Meanwhile, Tgno is, for example, 50° C. or more and 180° C. or less, preferably 80° C. or more and 160° C. or less, and more preferably 90° C. or more and 150° C. or less.
[0092] Next, the thickness distribution of the liquid crystal layer 6 according to this embodiment will be described with reference to Fig. 9. In Fig. 9, as viewed in the Z-axis direction, a first virtual line L1 is a virtual line that passes through the center of gravity P0 and is parallel to the slow axis. Also, as viewed in the Z-axis direction, a second virtual line L2 is a virtual line that passes through the center of gravity P0 and is parallel to the fast axis.
[0093] When viewed in the Z-axis direction, the dividing line L3 divides each line segment connecting the center of gravity P0 and each point on the periphery of the curved surface 21 at a ratio of 4:1 from the center of gravity P0 side to the periphery of the curved surface 21. Also, when viewed in the Z-axis direction, the first virtual line L1 and the dividing line L3 intersect at a first point P1 and a second point P2, and the second virtual line L2 and the dividing line L3 intersect at a third point P3 and a fourth point P4.
[0094] The distance between the first point P1 and the center of gravity P0 is 0.8 times X1. X1 is the distance between the center of gravity P0 and the intersection point between a line extending from the center of gravity P0 in the positive direction of the X-axis and the periphery of the curved surface 21. The distance between the second point P2 and the center of gravity P0 is 0.8 times X2. X2 is the distance between the center of gravity P0 and the intersection point between a line extending from the center of gravity P0 in the negative direction of the X-axis and the periphery of the curved surface 21.
[0095] The distance between the third point P3 and the center of gravity P0 is 0.8 times Y1. Y1 is the distance between the center of gravity P0 and the intersection point between a line extending from the center of gravity P0 in the positive direction of the Y axis and the periphery of the curved surface 21. The distance between the fourth point P4 and the center of gravity P0 is 0.8 times Y2. Y2 is the distance between the center of gravity P0 and the intersection point between a line extending from the center of gravity P0 in the negative direction of the Y axis and the periphery of the curved surface 21.
[0096] According to this embodiment, the sum of the thicknesses ty1, ty2 of the liquid crystal layer 6 at the third point P3 and the fourth point P4 on the second virtual line L2 shown in Fig. 9 is smaller than the sum of the thicknesses tx1, tx2 of the liquid crystal layer 6 at the first point P1 and the second point P2 on the first virtual line L1. In other words, the following formula (1) is established.
[0097]
number
[0098] The thickness of the liquid crystal layer 6 is measured in the normal direction at each point on the curved surface 21 of the lens 2. The thickness of the liquid crystal layer 6 is calculated, for example, from spectral interference or from a scanning electron microscope (SEM) photograph.
[0099] In addition to the above formula (1), the following formula (2) preferably holds:
[0100]
number
[0101] In this embodiment, the thickness distribution of the liquid crystal layer 6 is controlled by the anisotropy of the elongation of the retarder 3 during bending, but the thickness distribution of the liquid crystal layer 6 may be controlled by dry etching. As the dry etching, for example, plasma etching is used.
[0102] The dry etching method is performed, for example, before bending. For example, as shown in Figures 10(A) and 10(B), in the plasma etching method, a mask M that covers a part of the liquid crystal layer 6 is used to etch the exposed part of the liquid crystal layer 6 with plasma such as oxygen. The mask M is preferably made of glass, which has excellent etching resistance and rigidity. A plurality of masks M of different sizes may be used in sequence so that the thickness T3 of the liquid crystal layer 6 changes smoothly.
[0103] In the plasma etching method, for example, a RIE (Reactive Ion Etching) device is used. The gas used to generate the plasma contains, for example, oxygen gas, and may further contain a halogen-containing gas such as CF4 or CCl4 in addition to oxygen gas. The amount of etching can be controlled by the etching time and gas flow rate.
[0104] Third embodiment Next, the optical element 1 according to the third embodiment will be described. The following mainly describes the differences from the first and second embodiments. Note that the technology of this embodiment may be combined with one or more of the technology of the first and second embodiments.
[0105] First, an optical element 1C according to a third embodiment will be described with reference to Fig. 11 and Fig. 12. In Fig. 11C and Fig. 12C, the magnitude of Rd is expressed in gray scale. As the color approaches black from white, the magnitude of Rd of the optical element 1C increases.
[0106] The optical element 1C according to the third embodiment includes a lens 2C and a retardation plate 3C. The retardation plate 3C includes a transparent substrate 4C, an alignment layer 5C, and a liquid crystal layer 6C. The lens 2C and the retardation plate 3C are bonded together via, for example, a bonding layer 7C.
[0107] When the retarder 3C is bent, the extension rate of the retarder 3C differs between the periphery and the center of the retarder 3C. As a result, the thickness of the retarder 3C and the thickness of the liquid crystal layer 6C change concentrically. Therefore, Rd shifts concentrically, and the color tone shifts concentrically. The extension rate (%) can be calculated from the formula "(A2-A1) / A1×100" where A1 is the dimension before bending and A2 is the dimension after bending.
[0108] For example, in the case where the curved surface 21C of the lens 2C is a concave surface as shown in Fig. 11(A), when the retarder 3C is bent as shown in Fig. 11(B), the thickness of the retarder 3C becomes continuously thinner from the periphery to the center of the retarder 3C. This is because the timing at which the periphery and the center of the retarder 3C come into contact with the curved surface 21C differs, and the center of the retarder 3C comes into contact with the curved surface 21C later than the periphery.
[0109] Therefore, as shown in Fig. 11(B), the thickness of the liquid crystal layer 6C becomes continuously thinner from the periphery to the center of the liquid crystal layer 6C. As a result, Rd becomes continuously smaller from the periphery to the center of the liquid crystal layer 6C as shown in Fig. 12(C). Therefore, the color tone shifts concentrically.
[0110] In addition, when the curved surface 21C of the lens 2C is a convex curved surface as shown in Fig. 12(A), if the retarder 3C is bent as shown in Fig. 12(B), the thickness of the retarder 3C will be continuously thinner from the center to the periphery of the retarder 3C. This is because the timing at which the periphery and the center of the retarder 3C come into contact with the curved surface 21C differs, and the periphery of the retarder 3C comes into contact with the curved surface 21C later than the center.
[0111] Therefore, as shown in Fig. 12(B), the thickness of the liquid crystal layer 6C becomes continuously thinner from the center to the periphery of the liquid crystal layer 6C. As a result, Rd becomes continuously smaller from the center to the periphery of the liquid crystal layer 6C as shown in Fig. 12(C). Therefore, the color tone shifts concentrically.
[0112] 13 and 14, an optical element 1 according to this embodiment includes a lens 2 and a retardation plate 3. The retardation plate 3 includes a transparent substrate 4, an alignment layer 5, and a liquid crystal layer 6. The lens 2 and the retardation plate 3 are bonded together via, for example, an adhesive layer 7. The alignment layer 5 has a plurality of grooves 51 parallel to each other on a surface in contact with the liquid crystal layer 6.
[0113] When bending the retarder 3, the extension rate of the retarder 3 differs between the periphery and the center of the retarder 3. As a result, similarly to the third reference embodiment, after bending the retarder 3, the thickness T4 of the retarder 3 and the thickness T3 of the liquid crystal layer 6 differ between the periphery and the center of the retarder 3.
[0114] For example, in the case where the curved surface 21 of the lens 2 is a concave curved surface as shown in FIG. 13(A), when the retardation film 3 is bent, as described in the third reference embodiment, the thickness T4 of the retardation film 3 and the thickness T3 of the liquid crystal layer 6 become continuously thinner from the periphery to the center of the retardation film 3.
[0115] When the curved surface 21 of the lens 2 is a concave curved surface, the elongation of the retarder 3 is as follows. The elongation of the retarder 3 at the periphery of the retarder 3 is, for example, 0.1% to 20%, and preferably 1% to 20%. The elongation of the retarder 3 at the center of the retarder 3 is, for example, 0.5% to 30%, and preferably 1% to 20%.
[0116] Furthermore, in the case where the curved surface 21 of the lens 2 is a convex curved surface as shown in FIG. 14(A), when the retardation film 3 is bent, as described in the third reference embodiment, the thickness T4 of the retardation film 3 and the thickness T3 of the liquid crystal layer 6 become continuously thinner from the center to the periphery of the retardation film 3.
[0117] When the curved surface 21 of the lens 2 is a convex curved surface, the elongation of the retardation film 3 is as follows. The elongation of the retardation film 3 at the center of the retardation film 3 is, for example, 0.1% to 20%, and preferably 1% to 20%. The elongation of the retardation film 3 at the periphery of the retardation film 3 is, for example, 0.5% to 30%, and preferably 1% to 20%.
[0118] These tendencies also occur when the retarder 3 has anisotropy in the stretching in the X-axis direction and the Y-axis direction as in the second embodiment. For example, on the second virtual line L2 in Fig. 9, the thickness T4 of the retarder 3 and the thickness T3 of the liquid crystal layer 6 continuously become thinner or thicker from the periphery of the retarder 3 toward the center. The same tendency also occurs on the first virtual line L1 in Fig. 9. This tendency is particularly noticeable on the second virtual line L2 in Fig. 9.
[0119] Therefore, in the optical element 1 of this embodiment and the like, the depth D of the groove 51 at the portion where the thickness T4 of the retardation plate 3 is the thinnest is deeper than the depth D of the groove 51 at the portion where the thickness T4 of the retardation plate 3 is the thickest. The depth D of the groove 51 is adjusted, for example, by the concave-convex pattern of a mold used in the imprinting method. The depth D of the groove 51 can also be adjusted by partially ashing the surface of the alignment layer 5.
[0120] The deeper the depth D of the groove 51, the stronger the alignment control force of the liquid crystal molecules in the liquid crystal layer 6 and the larger Δn. The increase in Rd due to the increase in Δn can offset the decrease in Rd due to the decrease in d, and the variation in Rd can be suppressed.
[0121] For example, when the curved surface 21 of the lens 2 is a concave curved surface as shown in Fig. 13(A), as is clear from a comparison between Fig. 13(B) and Fig. 13(C), the depth D of the groove 51 at the center of the retardation film 3 is deeper than the depth D of the groove 51 at the periphery of the retardation film 3. The depth D of the groove 51 becomes deeper continuously or stepwise from the periphery to the center of the retardation film 3. Therefore, it is possible to suppress a concentric shift of Rd and a concentric shift of color tone.
[0122] Furthermore, when the curved surface 21 of the lens 2 is a convex curved surface as shown in Fig. 14(A), as is clear from a comparison of Fig. 14(B) and Fig. 14(C), the depth D of the grooves 51 at the periphery of the retardation film 3 is deeper than the depth D of the grooves 51 at the center of the retardation film 3. The depth D of the grooves 51 becomes deeper continuously or stepwise from the center to the periphery of the retardation film 3. Therefore, it is possible to suppress a concentric shift in Rd and a concentric shift in color tone.
[0123] As described above, the difference in thickness T4 of the retarder 3 and the difference in thickness T3 of the liquid crystal layer 6 are larger between the periphery and the center of the retarder 3 on the second virtual line L2 in Fig. 9 than on the first virtual line L1 in Fig. 9. Therefore, it is preferable that, at least on the second virtual line L2, the depth D of the groove 51 at the portion where the thickness T4 of the retarder 3 is the thinnest is deeper than the depth D of the groove 51 at the portion where the thickness T4 of the retarder 3 is the thickest. EXAMPLES
[0124] The experimental data will be explained below.
[0125] <Material> Monomer 1: Shin-Nakamura Chemical Co., Ltd. product name "NK Ester A-DCP", dimethylol-tricyclodecane diacrylate Monomer 2: Shin-Nakamura Chemical Co., Ltd. product name "NK Ester A-HD-N", 1,6-hexanediol diacrylate Monomer 3: Kyoeisha Chemical Co., Ltd. product name "Light Acrylate 4EG-A" triethylene glycol diacrylate Monomer 4: Tokyo Chemical Industry Co., Ltd. Product name Trimethylolpropane trimethacrylate Monomer 5: Shin Nakamura Chemical Co., Ltd. product name "U-6LPA" Monomer 6: Tokyo Chemical Industry Co., Ltd. Product name: "Tetrahydrofurfuryl acrylate" Liquid crystal 1: BASF product name "LC242" Photopolymerization initiator 1: Ciba Specialty Chemicals product name "IRGACURE907" Solvent 1: Methyl ethyl ketone Transparent substrate 1: PMMA film (Okura Kogyo Co., Ltd., OXIS FZ-T13-W1-40 Thickness: 40μm Transparent substrate 2: TAC film (Fujifilm ZRD40SL, thickness 40 μm).
[0126] <Photocurable composition 1> 20 g of monomer 2, 50 g of monomer 3, 30 g of monomer 4, and 3.0 g of photopolymerization initiator 1 were mixed together to prepare photocurable composition 1.
[0127] <Photocurable composition 2> 70 g of Monomer 1, 10 g of Monomer 2, 20 g of Monomer 5, and 3.0 g of Photopolymerization Initiator 1 were mixed together to prepare Photocurable Composition 2.
[0128] <Photocurable composition 3> 50 g of Monomer 1, 50 g of Monomer 5, and 3.0 g of Photopolymerization Initiator 1 were mixed together to prepare Photocurable Composition 3.
[0129] <Photocurable composition 4> 20 g of Monomer 1, 60 g of Monomer 2, 20 g of Monomer 5, and 3.0 g of Photopolymerization Initiator 1 were mixed together to prepare Photocurable Composition 4.
[0130] <Liquid crystal composition 1> 100 g of liquid crystal 1 and 3.0 g of photopolymerization initiator 1 were mixed, and the resulting mixture was diluted with solvent 1 so that the solid content concentration was 25 mass %, so that liquid crystal composition 1 was obtained.
[0131] <Liquid crystal composition 2> 50 g of liquid crystal 1, 50 g of monomer 6, and 3.0 g of photopolymerization initiator 1 were mixed, and the resulting mixture was diluted with solvent 1 so that the solid concentration was 50 mass %, so that liquid crystal composition 2 was obtained.
[0132] <Mold A> As mold A, a resin mold manufactured by Soken Chemical & Engineering Co., Ltd. (LSP70-140, groove pitch 140 nm, groove depth 150 nm) was prepared.
[0133] <Mold B> Mold B was prepared by the following procedure: First, the photocurable composition 2 was sandwiched between mold A and a PET film (Cosmoshine A4300 manufactured by Toyobo Co., Ltd., thickness 250 μm), and 1000 mJ / cm 2 was applied to the photocurable composition 2 through the PET film while maintaining the gap at 5 μm. 2 The mold was irradiated with ultraviolet light of 1000 nm to cure the photocurable composition 2. Thereafter, the mold A was peeled off to prepare the mold B. The concave-convex pattern of the mold B was the inverse of the concave-convex pattern of the mold A.
[0134] <Mold C> Mold C was produced by the following procedure. First, a disk-shaped mask was placed in the center of mold B, and mold B was ashed in a vacuum with oxygen at 200 ml / min and output of 400 W. Then, photocurable composition 1 was sandwiched between mold B and a PET film (Cosmoshine A4300 manufactured by Toyobo Co., Ltd., thickness 250 μm), and 1000 mJ / cm was applied to photocurable composition 1 through the PET film while maintaining the gap at 5 μm. 2 The photocurable composition 1 was cured by irradiating it with ultraviolet light of 100 nm. Thereafter, mold B was peeled off to prepare mold C. The concave-convex pattern of mold C was the inverse of the concave-convex pattern of mold B. The concave-convex pattern of mold C was a square with sides of 80 mm in plan view, with the groove depth at the center being 95 nm and the groove depth 40 mm outward from the center being 25 nm.
[0135] <Optical elements> In the following Examples 1 to 8, optical elements were produced using the above materials and the above molds. The following Examples 1, 2, 5, 6 and 8 are working examples, and the following Examples 3, 4 and 7 are comparative examples.
[0136] (Example 1) The alignment layer was prepared by the following procedure: First, the photocurable composition 1 was sandwiched between the mold A and the transparent substrate 1, and 1000 mJ / cm 2 was applied to the photocurable composition 1 through the transparent substrate 1 while maintaining the gap between them at 5 μm. 2The photocurable composition 1 was cured by irradiating it with ultraviolet light. Thereafter, the mold A was peeled off to produce a laminate of the alignment layer 1 having the unevenness formed thereon and the transparent substrate 1. The alignment layer 1 had a groove pitch of 140 nm and a groove depth of 140 nm.
[0137] The liquid crystal layer was prepared by the following procedure. First, the above liquid crystal composition 1 was applied by spin coating to the uneven surface of the alignment layer, and dried at 90°C for 5 minutes to form a liquid film with a thickness of 1 μm. 2 The liquid film was irradiated with ultraviolet light to cure the liquid crystal composition 1. In this way, a retardation plate including a liquid crystal layer, an alignment layer, and a transparent substrate was obtained.
[0138] The optical element was fabricated by the following procedure. First, a plano-concave lens (manufactured by Edmund Optics, product code #45-038, diameter 50 mm) was prepared as a lens. Next, an optical adhesive (manufactured by PANAC, PDS1, thickness 25 μm) was attached to the surface of the transparent substrate of the retardation plate. After that, inside the vacuum vessel, the concave surface of the plano-concave lens was facing upward, and the retardation plate was placed above it. The retardation plate was placed horizontally with the optical adhesive facing downward. Next, the inside of the vacuum vessel was evacuated, and the retardation plate was brought into contact with the concave surface of the plano-concave lens in a state of being heated to 115° C., and the retardation plate was pressed against the concave surface with an air pressure of 300 kPa, and the retardation plate was bent. In this way, an optical element was obtained.
[0139] (Example 2) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition 2 was used instead of Photocurable Composition 1.
[0140] (Example 3) An optical element was prepared in the same manner as in Example 1, except that SIR-W044AP (liquid crystal composition 3) manufactured by Osaka Organic Chemical Industry Co., Ltd. was used instead of liquid crystal composition 1, and the thickness of the liquid crystal layer was set to 1 μm.
[0141] (Example 4) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition 3 was used instead of Photocurable Composition 1.
[0142] (Example 5) An optical element was produced in the same manner as in Example 4, except that the transparent substrate 2 was used instead of the transparent substrate 1 and the retardation plate was heated to 145°C.
[0143] (Example 6) An optical element was produced in the same manner as in Example 1, except that Photocurable Composition 4 was used instead of Photocurable Composition 1.
[0144] (Example 7) An optical element was prepared in the same manner as in Example 1, except that transparent substrate 2 was used instead of transparent substrate 1, liquid crystal composition 2 was used instead of liquid crystal composition 1, the thickness of the liquid crystal layer was 2 μm, and the retardation plate was heated to 145° C.
[0145] (Example 8) An optical element was produced in the same manner as in Example 1, except that the alignment layer was produced using mold C instead of mold A.
[0146] <Glass transition temperature> The glass transition points of the transparent substrate and the retardation plate were measured by TMA according to the following procedure. A sample with a length of 8 mm and a width of 5 mm was attached to the TMA, and the tensile force in the longitudinal direction was maintained at 0.2 N. The temperature was raised from 30°C to 200°C at a rate of 5°C / min, and the dimensional change of the sample was measured. The inflection point at which the elongation rate changes in the obtained TMA curve was used as a reference, and the intersection point between the extension of the straight line on the high temperature side and the extension of the straight line on the low temperature side was determined as the glass transition point. When there were two or more inflection points, the inflection point on the higher temperature side was determined as the glass transition point. The measurement was performed three times, and the arithmetic average value was determined as the glass transition point. When measuring Tgne, the length direction of the sample was parallel to the slow axis, and when measuring Tgno, the length direction of the sample was parallel to the fast axis.
[0147] <Young's modulus> The Young's modulus of the transparent substrate and the retardation plate was measured by TMA measurement according to the following procedure. A sample with a length of 8 mm and a width of 5 mm was attached to the TMA, and the tensile force in the longitudinal direction was increased from 0.01 N to 1 N at a rate of 0.02 N / min, and the dimensional change of the sample was measured. When the transparent substrate was PMMA, the temperature of the sample was adjusted to 115°C in advance. When the transparent substrate was TAC, the temperature of the sample was adjusted to 145°C in advance. The Young's modulus was calculated in the region of strain 0.0125 to 0.05. The measurement was performed three times, and the arithmetic average value was obtained as the Young's modulus. When measuring Ene, the longitudinal direction of the sample was parallel to the slow axis, and when measuring Eno, the longitudinal direction of the sample was parallel to the fast axis.
[0148] <Evaluation of optical elements> The optical elements produced in Examples 1 to 5 and 8 were visually inspected to check for the presence or absence of buckling of the retardation plate. The results are shown in Table 1.
[0149] [Table 1] As is clear from Table 1, in Examples 1, 2, 5, and 8, Ene / Ef and Eno / Ef were 5.00 or less, so there was no buckling. On the other hand, in Examples 3 and 4, at least one of Ene / Ef and Eno / Ef was greater than 5.00, so there was buckling. A steep change in retardation was observed in the areas where buckling occurred.
[0150] The retardation Rd of the optical elements prepared in Examples 1, 5 to 7 was measured. Rd was measured using a two-dimensional birefringence evaluation device (Photonic Lattice, Inc., WPA-200) by setting the retardation plate facing the camera of the evaluation device and measuring the entire effective area (circular area with a diameter of 40 mm) of the retardation plate all at once. Rd is the retardation of light with a wavelength of 543 nm. The results are shown in Table 2.
[0151] [Table 2] In Table 2, Rne is the ratio (maximum / minimum) of the maximum value to the minimum value of Rd on the first virtual line L1 shown in Fig. 9, and Rno is the ratio (maximum / minimum) of the maximum value to the minimum value of Rd on the second virtual line L2 shown in Fig. 9. The closer Rne / Rno is to 1.00, the smaller the difference in Rd between the first point P1 and the second point P2 on the first virtual line L1 and the third point P3 and the fourth point P4 on the second virtual line L2. When Rne / Rno is greater than 0.95 and less than 1.05, it is determined that the distribution of Rd is isotropic (concentric).
[0152] As is clear from Table 2, in Examples 1, 5, and 6, Tgne was larger than Tgno, so Rne / Rno was larger than 0.95 and smaller than 1.05, and the distribution of Rd was isotropic. On the other hand, in Example 7, Tgne was the same as Tgno, so Rne / Rno was 1.05 or more, and the distribution of Rd was not isotropic (concentric).
[0153] The retardation Rd of the optical elements produced in Examples 1 and 8 was measured. The method for measuring Rd was as described above. The results are shown in Table 3.
[0154] [Table 3] In Table 3, D1 is the groove depth of the alignment layer at the point where the retarder is thinnest in the effective area of the retarder, and D2 is the groove depth of the alignment layer at the point where the retarder is thickest in the effective area of the retarder. Also in Table 3, D3 is the groove depth of the alignment layer at the point where the retarder is thinnest on the second virtual line L2 (see FIG. 9), and D4 is the groove depth of the alignment layer at the point where the retarder is thickest on the second virtual line L2.
[0155] In Table 3, Rmax is the maximum value of Rd in the entire effective area of the retardation film, and Rmin is the minimum value of Rd in the entire effective area of the retardation film. When 2×Rmax / (Rmax+Rmin) is 1.030 or less and 2×Rmin / (Rmax+Rmin) is 0.970 or more, it was determined that the in-plane variation of Rd is smaller.
[0156] As is clear from Table 3, in Example 8, D1 was larger than D2, so the in-plane variation of Rd was smaller than that of Example 1. In addition, in Example 8, D3 was larger than D4, so the in-plane variation of Rd was smaller than that of Example 1.
[0157] Although the optical element and the manufacturing method thereof according to the present disclosure have been described above, the present disclosure is not limited to the above-mentioned embodiments. Various changes, modifications, substitutions, additions, deletions, and combinations are possible within the scope of the claims. These naturally fall within the technical scope of the present disclosure.
[0158] This application claims priority based on Japanese Patent Application No. 2020-135092, filed with the Japan Patent Office on August 7, 2020, the entire contents of which are incorporated herein by reference. [Explanation of symbols]
[0159] 1 Optical elements 2 Lenses 3 Retardation plate 4 Transparent base material 5. Alignment layer 6 Liquid crystal layer
Claims
1. A lens having a curved surface; a retardation plate curved along the curved surface, the retardation plate includes a transparent substrate and a liquid crystal layer formed on the transparent substrate, The retardation plate has a slow axis and a fast axis, An optical element, wherein a glass transition point Tgne of the retardation plate in the slow axis direction is greater than a glass transition point Tgno of the retardation plate in the fast axis direction.
2. An optical element as described in claim 1, wherein, when the temperature of the retardation film is the glass transition point of the transparent substrate, the ratio (Ene / Ef) of the Young's modulus Ef of the transparent substrate to the Young's modulus Ene of the retardation film in the slow axis direction is 0.10 or more and 5.00 or less, and the ratio (Eno / Ef) of the Young's modulus Ef of the transparent substrate to the Young's modulus Eno of the retardation film in the fast axis direction is 0.10 or more and 5.00 or less.
3. the retardation plate includes an alignment layer formed between the transparent substrate and the liquid crystal layer, 3 . The optical element according to claim 1 , wherein the alignment layer has a plurality of grooves parallel to each other on a surface in contact with the liquid crystal layer when viewed from a normal direction at the center of gravity of the curved surface of the lens.
4. An optical element as described in claim 3, wherein the depth of the groove at the portion where the thickness of the retardation plate is the thinnest is deeper than the depth of the groove at the portion where the thickness of the retardation plate is the thickest.
5. An optical element as described in claim 3 or 4, wherein, on a virtual line passing through the center of gravity of the phase difference plate and parallel to the fast axis, the depth of the groove at the portion where the thickness of the phase difference plate is thinnest is deeper than the depth of the groove at the portion where the thickness of the phase difference plate is thickest.
6. The curved surface is a concave curved surface, 6. The optical element according to claim 4, wherein the depth of the grooves in the center of the retardation plate is greater than the depth of the grooves in the periphery of the retardation plate.
7. The curved surface is a convex curved surface, The optical element according to claim 4 , wherein a depth of the grooves at the periphery of the retardation plate is greater than a depth of the grooves at the center of the retardation plate.
8. A method for producing the optical element according to any one of claims 1 to 7, comprising the steps of: a retardation plate that is formed on the first substrate and is curved to fit the curved surface of the lens;
Citation Information
Patent Citations
Plastic liquid crystal panel for curved display and method of manufacturing the same
JP2003295164A
Optical element for observing three dimensional video image, glasses for observing three dimensional video image, and system for displaying three dimensional video image
JP2012003003A
Polarized glasses
JP2012032527A
Circular polarization lens for 3-d viewing, and glasses using the same
JP2013020079A
Stereoscopic eyewear with complex curvature
JP2013519108A